Case Report: Stress-Induced Childhood-Onset Neurodegeneration With Ataxia-Seizures Syndrome Caused by a Novel Compound Heterozygous Mutation in ADPRHL2 - Lu, Aijun; Dong, Chunxia; Chen, Bihong; Xie, Lei; Hu, Huaiqiang (Frontiers in Neurology, 2022)
ADPRHL2 gene mutations have been demonstrated as the cause of stress-induced childhood-onset neurodegeneration with variable ataxia and seizures (CONDSIAS), an autosomal recessive genetic disorder characterized by an abnormal gait, intellectual disability, seizures, ataxia, other nervous system degenerative diseases, and axonal sensorimotor neuropathy. Since first reported in 2018, ADP-ribosylhydrolase like 2 (ADPRHL2) gene mutations in previous cases were all diallelic homozygous. Here, we report a case of CONDSIAS with a novel compound heterozygous mutation in the ADPRHL2 gene. This patient is presented with autonomic nervous dysfunction manifested as polyuria, gastrointestinal disturbance, and sinus arrhythmia, which may be considered as new clinical manifestations in addition to the above classical manifestations. Muscle biopsy revealed myogenic lesions, which is a previously unreported feature.